Serum fatty acids profile and association with early-onset coronary artery disease - Chao Xuan; Qing-Wu Tian; Hui Li; Jun-Jie Guo; Guo-Wei He; Li-Min Lun (SAGE Publishing, 2021)
Background: Fatty acids (FAs) play crucial roles in modulating and preventing diseases in humans, including early-onset coronary artery disease (EOCAD). In this study, we aimed to provide a profile of FAs in the serum of EOCAD patients and identify potential EOCAD-associated FAs. Methods: In the first stage, we analyzed the FAs profiles in pooled samples of patients with EOCAD using gas chromatography-mass spectrometry. In the second stage, the serum levels of the candidate FAs were validated in EOCAD patients. Results: A total of 128 EOCAD patients and 64 controls were included in the study. Forty-nine serum FAs were quantified in pooled samples; three ω-3 FAs were identified to be associated with EOCAD. Moreover, results from the validation stage indicated that serum levels of docosahexaenoic acid (DHA) were significantly lower in EOCAD patients (55.43 ± 33.86 µg/ml) and myocardial infarction (MI) patients (47.49 ± 28.44 μg/ml) than those in the controls (70.65 ± 43.56 µg/ml). Multivariate regression analysis revealed that elevated serum DHA level was an independent protective factor for EOCAD [odds ratio (OR) = 0.8917, 95% confidence interval (CI): 0.879-0.957] and MI (OR = 0.835, 95% CI: 0.799-0.862). Decreased serum levels of docosapentaenoic acid (DPA) and eicosapentaenoic acid (EPA) were observed in the early-onset MI group. Conclusion: The study provided the serum FAs profile of EOCAD and confirmed that the decrease in serum levels of DHA, DPA, and EPA was associated with EOCAD. These findings might contribute to understanding the cardiovascular effects of FAs, particularly the protective effects of ω-3 polyunsaturated FAs.